2021
DOI: 10.1177/08404704211031264
|View full text |Cite
|
Sign up to set email alerts
|

Will telemedicine survive after COVID-19?

Abstract: During the last 20 years, telemedicine has evolved in Quebec despite several barriers. We studied how a university health centre in Montreal implemented a strategy to enhance the use of telemedicine with the deployment of appropriate infrastructures, continuous training, and the use of advanced technologies, before and during the pandemic. COVID-19 accelerated the use of telemedicine by overcoming some pre-existing barriers. However, telemedicine was mainly limited to a distance consultation during the pandemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 14 publications
(16 reference statements)
0
27
0
Order By: Relevance
“…Canada’s digital communication infrastructure is extensive, but limited cellular network coverage and internet bandwidth were barriers for virtual care in rural and remote areas, 2 , 11 , 14 , 28 , 35 although a study of the Ontario Telemedicine Network found that only 0.2% of visits using that system were missed due to technical difficulties. 18 Poor interoperability between EHR systems can also be a barrier to virtual care.…”
Section: Barriers To Virtual Healthcare Adoptionmentioning
confidence: 99%
“…Canada’s digital communication infrastructure is extensive, but limited cellular network coverage and internet bandwidth were barriers for virtual care in rural and remote areas, 2 , 11 , 14 , 28 , 35 although a study of the Ontario Telemedicine Network found that only 0.2% of visits using that system were missed due to technical difficulties. 18 Poor interoperability between EHR systems can also be a barrier to virtual care.…”
Section: Barriers To Virtual Healthcare Adoptionmentioning
confidence: 99%
“…At the onset of COVID-19, healthcare professionals and service providers quickly incorporated existing technologies and platforms to deliver care and home monitoring to manage risks of COVID-19 transmission associated with in-person interactions 1,[13][14][15] . Although telehealth (or telemedicine and telerehabilitation) sites have been in place for over two decades in Canada, virtual interactions became a preferred replacement for in-person medical appointments which became less feasible.…”
Section: Technology Adoption In Healthcarementioning
confidence: 99%
“…Telephone consultations are now reimbursed even if they are excluded from the definition of telehealth in the 2005 Act on health services and social services (LSSSS) (4,5). Procurement processes have been adapted and revised to accelerate the deployment of telehealth technologies in health organizations (22). The expenses inherent in the use of the technology were also largely covered by the MSSS (23,24).…”
Section: The Pandemic As a Catalyst For A "Not So Quiet" Revolution In Quebecmentioning
confidence: 99%
“…The expenses inherent in the use of the technology were also largely covered by the MSSS (23,24). Furthermore, Health Canada (the Canadian federal ministry of health) has accelerated the process of conformity assessment of technologies submitted by industry and their approval (22).…”
Section: The Pandemic As a Catalyst For A "Not So Quiet" Revolution In Quebecmentioning
confidence: 99%
See 1 more Smart Citation